KnowledgeBoat Logo

Mathematics

Taking A = 60° and B = 30°, verify that

(i) sin(A + B)cos A cos B=tan A + tan B\dfrac{\text{sin(A + B)}}{\text{cos A cos B}} = \text{tan A + tan B}

(ii) sin(A - B)sin A sin B=cot B - cot A\dfrac{\text{sin(A - B)}}{\text{sin A sin B}} = \text{cot B - cot A}

Trigonometrical Ratios

8 Likes

Answer

(i) To verify,

sin(A + B)cos A cos B=tan A + tan B\dfrac{\text{sin(A + B)}}{\text{cos A cos B}} = \text{tan A + tan B}.

Substituting value of A and B in L.H.S. of the equation, we get :

sin(A + B)cos A cos Bsin(60° + 30°)cos 60° cos 30°sin 90°12×3213443.\Rightarrow \dfrac{\text{sin(A + B)}}{\text{cos A cos B}} \\[1em] \Rightarrow \dfrac{\text{sin(60° + 30°)}}{\text{cos 60° cos 30°}} \\[1em] \Rightarrow \dfrac{\text{sin 90°}}{\dfrac{1}{2} \times \dfrac{\sqrt{3}}{2}} \\[1em] \Rightarrow \dfrac{1}{\dfrac{\sqrt{3}}{4}} \\[1em] \Rightarrow \dfrac{4}{\sqrt{3}}.

Substituting value of A and B in R.H.S. of the equation, we get :

tan A + tan Btan 60° + tan 30°3+133+1343.\Rightarrow \text{tan A + tan B} \\[1em] \Rightarrow \text{tan 60° + tan 30°} \\[1em] \Rightarrow \sqrt{3} + \dfrac{1}{\sqrt{3}} \\[1em] \Rightarrow \dfrac{3 + 1}{\sqrt{3}} \\[1em] \Rightarrow \dfrac{4}{\sqrt{3}}.

Since, L.H.S. = R.H.S.

Hence, proved that sin(A + B)cos A cos B=tan A + tan B\dfrac{\text{sin(A + B)}}{\text{cos A cos B}} = \text{tan A + tan B}.

(ii) To verify,

sin(A - B)sin A sin B=cot B - cot A\dfrac{\text{sin(A - B)}}{\text{sin A sin B}} = \text{cot B - cot A}

Substituting value of A and B in L.H.S. of the equation, we get :

sin(A - B)sin A sin Bsin(60° - 30°)sin 60° sin 30°sin 30°sin 60° sin 30°1232×12123442323.\Rightarrow \dfrac{\text{sin(A - B)}}{\text{sin A sin B}} \\[1em] \Rightarrow \dfrac{\text{sin(60° - 30°)}}{\text{sin 60° sin 30°}} \\[1em] \Rightarrow \dfrac{\text{sin 30°}}{\text{sin 60° sin 30°}} \\[1em] \Rightarrow \dfrac{\dfrac{1}{2}}{\dfrac{\sqrt{3}}{2} \times \dfrac{1}{2}} \\[1em] \Rightarrow \dfrac{\dfrac{1}{2}}{\dfrac{\sqrt{3}}{4}} \\[1em] \Rightarrow \dfrac{4}{2\sqrt{3}} \\[1em] \Rightarrow \dfrac{2}{\sqrt{3}}.

Substituting value of A and B in R.H.S. of the equation, we get :

⇒ cot B - cot A

⇒ cot 30° - cot 60°

313=313\sqrt{3} - \dfrac{1}{\sqrt{3}} = \dfrac{3 - 1}{\sqrt{3}}

23\dfrac{2}{\sqrt{3}}.

Since, L.H.S. = R.H.S.

Hence, proved that sin(A - B)sin A sin B=cot B - cot A\dfrac{\text{sin(A - B)}}{\text{sin A sin B}} = \text{cot B - cot A}.

Answered By

4 Likes


Related Questions